IT Management Framework for Municipalities - Camargo Ariza, Luis Leonardo; Gasca Mantilla, Maira Cecilia; Medina Delgado, Byron (Data and Metadata, 2025)
The integration of information technology (IT) into urban processes can significantly enhance public management by providing objective and timely information for decision-making at all levels of governance. It facilitates the administration and control of city resources, strengthens processes, and fosters greater citizen participation, efficiency, and transparency in their execution. This article proposes an IT management framework aligned with the smart city concept. The framework was organized into three levels of IT management: strategic, tactical, and operational, which corresponded to the city’s maturity, intelligence, and technology, respectively. The model was based on best practices, international IT standards, and recognized theories. It was developed from the results of an instrument designed to quantify the indicators of two research variables: IT management and smart city, applied to the governing bodies of the city of Santa Marta, Colombia. The analysis of the responses allowed us to quantitatively and qualitatively describe the research variables and their interrelations. It also enabled us to identify strengths and weaknesses in order to make recommendations to improve the technological state and the development of services that increase the level of intelligence from the city of Santa Marta.